2007
DOI: 10.1007/s00429-007-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of vesicular glutamate transporters 1 and 2, glutamic acid decarboxylase and calretinin in rat entorhinal cortex

Abstract: We studied the distribution and coexpression of vesicular glutamate transporters (VGluT1, VGluT2), glutamic acid decarboxylase (GAD) and calretinin (CR, calcium-binding protein) in rat entorhinal cortex, using immunofluorescence staining and multichannel confocal laser scanning microscopy. Images were computer processed and subjected to automated 3D object recognition, colocalization analysis and 3D reconstruction. Since the VGluTs (in contrast to CR and GAD) occurred in fibers and axon terminals only, we focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…In a separate paper, we reported the details of the distribution of vesicular glutamate transporters 1 and 2 in the entorhinal cortex and reported coexpression of VGluT2 and CR (Wouterlood et al, 2007). In agreement with the previous findings, VGluT2 and CR coexpression was observed in axon terminals in the entorhinal cortex.…”
Section: General Distribution Of Vglut2 In Entorhinal Cortexsupporting
confidence: 89%
See 2 more Smart Citations
“…In a separate paper, we reported the details of the distribution of vesicular glutamate transporters 1 and 2 in the entorhinal cortex and reported coexpression of VGluT2 and CR (Wouterlood et al, 2007). In agreement with the previous findings, VGluT2 and CR coexpression was observed in axon terminals in the entorhinal cortex.…”
Section: General Distribution Of Vglut2 In Entorhinal Cortexsupporting
confidence: 89%
“…In an earlier study, we observed CR-GABA coexpressing neuronal cell bodies in the entorhinal cortex intermingled with CR positive, GABA-negative cell bodies (Wouterlood et al, 2000). In a follow-up study on this cortical area, we noted the presence of axon terminals that coexpressed CR and VGluT2 (Wouterlood et al, 2007). Thus it is conceivable that CR-VGluT2-positive axon terminals belong to the intrinsic CR-positive and GABAnegative entorhinal neurons.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The parvalbumin cells in the superficial layers of this region are exclusively GABAergic (Wouterlood et al, 1995). The majority of calretinin neurons were initially thought to be GABAergic but several reports found also calretinin positive glutamatergic neurons (Miettinen et al, 1997; Wouterlood et al, 2000, 2007, 2008). Hence, based on the overall distribution of GABAergic neurons in the parahippocampal region, it is likely that the densely clustered calretinin positive neurons in the mMEC are glutamatergic (Miettinen et al, 1997), but their transmitter identity remains to be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…The following commercial antibodies were used: 1. anti-vGluT-1 polyclonal antibody, raised in guinea pig against a synthetic linear peptide from rat vGluT-1 (Millipore, Billerica, MA, USA) [34,64]; 2. anti-vGluT-2 polyclonal antibody, raised in rabbit against a strep-tag fusion protein of rat vGluT-2 (Synaptic System, Goettingen, Germany) [34,65]; 3. (a) anti-GAD monoclonal antibody, raised in mouse against human GAD-65-GST fusion protein (Stressgen, Victoria, BC, Canada), and (b) anti-GAD polyclonal antibody, raised in rabbit against a synthetic peptide corresponding to the rat GAD-65 C-terminus residues 572-585 (Chemicon), which react to both GAD-65 and GAD-67 [63]; 4.…”
Section: Methodsmentioning
confidence: 99%